A especialização lato sensu em neuropsicologia na cidade de Goiânia: dilemas ético-políticos - Costa, Valéria Barros (2019)
The present master's dissertation reports a research on postgraduate education in Neuropsychology in the city of Goiania, with focus in the more general context of the expansion of higher education in Psychology, as well as the historical constitution of Historical-Cultural Neuropsychology. In order to do so, it started from the following questions: a) When did neuropsychology reach relevance in Goiânia? b) What epistemological perspectives are present in the lato sensu Postgraduate courses in Neuropsychology in the city of Goiania? c) What ethical-political challenges are present in the format of the post-graduation lato sensu in Neuropsychology with regard to the confrontation of the phenomenon "medicalization of life"? These questions was approached through a qualitative methodology, which involves the bibliographic research about the object under study, the theoretical approach used, as well as the search in official websites and analysis of the projects of three lato sensu courses and the recording of interviews with its managers, which were organized with the methodology of the Nuclei of Signification. The records were arranged in four nuclei: a) determining factors for the constitution of a course manager; b) senses about fundamental themes that permeate the training in Neuropsychology; c) discussions in the theoretical and methodological field of the training in Neuropsychology; d) ethical-political discussions. Our conclusions point to the historical mark of liberalism / neoliberalism in the offer of the lato sensu postgraduate course in neuropsychology, which expanded beyond public control until reaching the number of eight face-to-face courses in Goiânia. The courses show a reproduction of the medical model of action, with the predominance of an eclectic, organic, medicalizing model, focused on the psychometric diagnosis, at the expense of the promotion of the quality of life, the understanding of education as a social process that transforms the brain as well and the training of professionals for neuropsychological rehabilitation. We also consider that these characteristics are opposed to the historical-cultural perspective; to its appreciation of the analysis of the complex functional systems of the human brain, resulting from the individual's cultural formation.